RANCANG BANGUN KOMPONEN UTAMA PLTS OFF-GRID UNTUK MENUNJANG OPERASI INCINERATOR SIPESAT® - Noor Hidayati; Arifia Ekayuliana (Jurnal Poli-Teknologi, 2021)
To increase reliability of SIPESAT® Incinerator, off-grid solar powerplant was installed. The aim of this paper is to designing the requirement of the main equipment for the solar powerplant. 270 w, 3 autonomies days were used as the main parameter. GHI gathered from NASA’s data, VRLA battery type with MPPT inverter type was chosen to design the solar powerplant system. based on calculation results, the solar powerplant system need two solar panels 150watt each, and two VRLA battery 24V 200 Ah each,